Characteristics and outcomes of patients requiring bailout use of glycoprotein IIb/IIIa inhibitors for thrombotic complications of percutaneous coronary intervention: An analysis from the CHAMPION PHOENIX trial. (1st March 2019) - Abtan, Jeremie; Ducrocq, Gregory; Steg, Ph. Gabriel; Stone, Gregg W.; Mahaffey, Kenneth W.; Gibson, C. Michael; Hamm, Christian; Price, Matthew J.; Prats, Jayne; Elkin, Steven; Deliargyris, Efthymios N.; White, Harvey D.; et al.
Abstract: Aims: To describe the characteristics and outcomes of patients receiving bailout glycoprotein IIb/IIIa inhibitors (GPI) for thrombotic complications of percutaneous coronary intervention (PCI) in a large, contemporary trial. Methods and results: In the CHAMPION PHOENIX trial, the use of GPI was restricted to bailout for thrombotic complications. We describe the characteristics and outcomes of patients requiring bailout GPI compared to patients not receiving GPIs, with adjustment through propensity-score. A multivariable model was constructed to identify independent correlates associated with bailout GPI use. A total of 380 out of 10, 942 patients received GPI (3.5%); GPI patients were younger, more frequently male, more likely to present with ST segment elevation myocardial infarction and less frequently treated with cangrelor. At 48 h, GPI patients experienced higher rates of the primary composite outcome of death, myocardial infarction, ischemia-driven revascularization, or stent thrombosis (ST) (19.2% vs 4.8%; adjusted OR: 5.65(4.08, 7.82), p  < 0.0001) and a higher rate of GUSTO severe or moderate bleeding (2.6% vs 0.4% adjusted OR: 4.90 (1.98, 12.18), p  = 0.0006) compared with non GPI patients. Independent correlates of GPI use were STEMI, use of unfractionated heparin, drug-eluting stents and longer procedure duration. Conclusions: In a large contemporary trial, patients receiving bailout GPI for thrombotic complications of PCI experienced very high risks of both ischemic and bleeding complications, suggesting that prevention of periprocedural complications rather than bailout GPI may be preferable. Clinical Trial Registration:http://www.clinicaltrials.gov identifier:NCT01156571 . Highlights: This is a contemporary description of glycoprotein IIb/IIIa inhibitors as bail-out therapy in PCI according to international guidelines. Despite the use of GPI, patients experienced poor outcomes both in terms of ischemia and bleeding. GPIs may be too little too late. Prevention of periprocedural complications seems more desirable than cure. In that respect, the observation that cangrelor reduced the need for bailout GPI is potentially clinically important.